2021
DOI: 10.3389/fnagi.2021.645258
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training-Related Changes in Cortical Gray Matter Diffusivity and Cognitive Function in Mild Cognitive Impairment and Healthy Older Adults

Abstract: Individuals with Mild Cognitive Impairment (MCI) are at an elevated risk of dementia and exhibit deficits in cognition and cortical gray matter (GM) volume, thickness, and microstructure. Meanwhile, exercise training appears to preserve brain function and macrostructure may help delay or prevent the onset of dementia in individuals with MCI. Yet, our understanding of the neurophysiological effects of exercise training in individuals with MCI remains limited. Recent work suggests that the measures of gray matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 98 publications
4
17
0
Order By: Relevance
“…Our results also suggest that the increase in FC between the anterior insula and precuneus may be an important neural basis for the ET-induced enhancements in subjective well-being among older adults diagnosed with MCI. Consistent with our previous studies using the same MCI cohort that showed the ET-related effects were evident in the insula ( Chirles et al, 2017 ; Alfini et al, 2019 ; Callow et al, 2021 ), our work collectively suggests that the insula is a brain region that is particularly impacted by ET in individuals with MCI. While most MCI studies have focused on improvement in cognitive function, the present study extends the existing literature by suggesting that the neuroprotective effects induced by exercise may be extended to the psychological well-being of older adults with MCI.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also suggest that the increase in FC between the anterior insula and precuneus may be an important neural basis for the ET-induced enhancements in subjective well-being among older adults diagnosed with MCI. Consistent with our previous studies using the same MCI cohort that showed the ET-related effects were evident in the insula ( Chirles et al, 2017 ; Alfini et al, 2019 ; Callow et al, 2021 ), our work collectively suggests that the insula is a brain region that is particularly impacted by ET in individuals with MCI. While most MCI studies have focused on improvement in cognitive function, the present study extends the existing literature by suggesting that the neuroprotective effects induced by exercise may be extended to the psychological well-being of older adults with MCI.…”
Section: Discussionsupporting
confidence: 92%
“…We observed decreased MD after anodal compared to sham group for individuals with initially lower MD in the stimulation target, possibly indicating increases in tissue density (due to reshaping of neuronal or glial processes) or enhanced tissue organization (due to strengthened dendrites or axons) due to tDCS 5,41 . Numerically, MD values suggested a slight increase from before to after the intervention, similar to what has been observed after exersice training in older adults: For example, Callow and colleagues found increases in cortical grey matter (insular) MD after training 42 . These training-induced MD increases were interpreted as reduced in ammation and cellular swelling in the aged brain 43,44 .…”
Section: Discussionsupporting
confidence: 64%
“…This suggests that including both structural and diffusion MRI measures increased our sensitivity to complementary underlying structural alterations. While the complexities of DWI underpinnings in grey matter remain as discussed above, our findings support a growing body of literature which demonstrates the utility of cortical DWI measurements to capture age- and cognitive-related variance ( Callow et al, 2021 ; Grydeland et al, 2013 ; Philippi et al, 2016 ; Radhakrishnan et al, 2022 ; Raz & Rodrigue, 2006 ; Reas et al, 2018 ; Rodriguez-Vieitez et al, 2021 ; Schneider et al, 2019 ). We also note that across all components identified as contributing to brain-cognition relationships, DWI metrics displayed a complementary nature.…”
Section: Discussionsupporting
confidence: 82%